2001
DOI: 10.1021/jo001515b
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Azines by the Reaction of a Nucleophilic Carbene with Diazoalkanes:  A Synthetic and Crystallographic Study

Abstract: Reactions of the nucleophilic carbene 1,3-dimesityl-imidazol-2-ylidene (1) with diazofluorene, diphenyldiazomethane, and azidotrimethylsilane were examined. Specifically, carbene 1 reacts with diazofluorene and diphenyldiazomethane to give addition products (azines: 3 and 4, respectively). Compounds 3 and 4 were further characterized in the solid-state by single-crystal X-ray crystallographic studies. [3 (a = 9.7936(6) A, b = 10.0529(7) A, c = 16.251(1) A, alpha = 75.765(1) degrees, beta = 79.711(1) degrees, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 17 publications
1
31
0
1
Order By: Relevance
“…Thus, the azines 3h,q and 4-8 studied by Clyburne et al 28,29 can be confirmed to be strongly polarized, p-delocalized materials which, in case extreme push-pull substitutions, should exhibit NLO behaviour.…”
Section: Bond Length and Occupation Coefficient For Quantifying The Pmentioning
confidence: 67%
See 2 more Smart Citations
“…Thus, the azines 3h,q and 4-8 studied by Clyburne et al 28,29 can be confirmed to be strongly polarized, p-delocalized materials which, in case extreme push-pull substitutions, should exhibit NLO behaviour.…”
Section: Bond Length and Occupation Coefficient For Quantifying The Pmentioning
confidence: 67%
“…Synthesis and characterization of azines 3-8 are published [24][25][26][27][28][29] ; all calculations were carried out on SGI workstations and LINUX clusters.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decomposition of carbene-azide adducts. 367 Analogues with donor and acceptor moieties on the molecule have also been obtained. 369 The azine fragment, depending on its substituents, can act as a conductor or breaker of the conjugation.…”
Section: Scheme 95 Addition Of Benzimidazol-2-ylidenes With Aryl Azimentioning
confidence: 99%
“…In recent years synthesis of organic compound has been use catalyst such as hexaaquaaluminium (III) tetrafluoroborate [2], ionic liquids [3] and modified zirconia [4] etc. Diimines (azines) are most required compounds; they are undergoing interesting reactions and applications [5]. Azine compounds have been used in medicinal and materials relevant applications such as anti-bacterial drugs [6], anti-malarial drugs [7] anti-fungal drugs [8], drug development [9], tumor growth inhibitors [10], optoelectronics [11], NLO [12] materials , light-control devices [13], organic semiconductors [14], tunable molecular devices [15].…”
Section: Introductionmentioning
confidence: 99%